PHARMACOLOGICAL EVALUATION OF ANTI-HYPERLIPIDAEMIC ACTIVITY OF VACHA CHURNA (ACORUS CALAMUS LINN.) AND MUSTA CHURNA (CYPERUS ROTUNDUS LINN.) - Kumar Singh, Anoop (International Journal of Ayurveda and Pharma Research, 2015)
Vacha is identified botanically as Acorus calmus Linn belongs to the family Araceae. In Pharmacological study was carried out on Wistar strain albino rats. The activity of the drug was analyzed under the following groups: Group I - Water control, Group II - Cholesterol control, Group III - Vacha Churna and Group IV - Musta Churna. Parameters like ponderal changes, histopathological study of organs, and biochemical parameters mainly the lipid profile were studied. In present study animals administered with hyperlipidaemic diet have shown increase in body weight in comparison to normal rats, however the observed increase is found to be statistically non-significant. Both the test drugs non-significantly attenuated the body weight, among them the magnitude of decreased bodyweight is more in Vacha treated group. In present study administration of hyperlipidaemic diet did not affect the weight if heart, liver and kidney to significant extent in comparison to normal rats. In test drug treated groups also the weight of these organs not affected to significant extent. Administration of Vacha churna and Musta churna did not affect serum lipid parameters in comparison to cholesterol control rats except on serum HDL cholesterol in which moderate attenuation was observed. The test drugs contrary to the expectation did not significantly lower neither the cholesterol nor the triglyceride level in the serum.